(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
The article addresses various aspects of Peruvian independence that had an impact on the period of the First Mexican Empire. Through the concept of experience, points of convergence and dissension between the emancipatory processes of both countries are shown. Four thematic nuclei are addressed: the American representation in the Spanish Courts, the role of religion, the problem of Hispanophobia and the defense of the monarchy.